How high-speed rail affects local land prices: Evidence from Taipei, China - Nuobu Renzhi (Asian Development Bank Institute (ADBI), 2019)
This paper evaluates the effect of high-speed rail (THSR) on the land prices of targeted regions (THSR regions) in Taipei,China using prefectural-level data from 1993 to 2017. The construction of THSR started in 2000 and was finished in 2006. The THSR line to Zuoying (Kaohsiung City) first operated in 2007. After station construction for Miaoli, Changhua, and Yunlin was complete at the end of 2015, the entire line was open in 2016. THSR investment has been believed to play an important role in changing land usage and value, but such spillover effects on land prices have not yet been evaluated formally. Employing the difference-in-difference (DID) methodology, I estimate the impact of THSR on local land prices by comparing the land prices in THSR regions with those of other regions not covered by THSR. The results suggest that THSR positively affected the average land prices in THSR regions from the start of construction, and such positive effect became even larger after the beginning of the operation. There does, however, appear to be an inequality in land price growth among THSR regions. The positive spillover effects in northern regions are larger than those in their southern counterparts, which indicates that some straw effects may exist in southern regions. Because increases in local land prices often lead to increased local tax revenues, this paper, by showing the positive relationship between THSR investment and land prices, may have meaningful implications for future potential THSR investments in other economies or regions.
Keywords: L92; R41; R53; R58; 330; high-speed rail; local land prices; transportation infrastructure